The Effect of Brand Image and Prosumer on Customer Satisfaction Madame Gie Beauty Brand - Meilinda Anggriana Porrie; Anindita Lintangdesi Afriani (CV Projurnal Mitra Publikasi, 2025)
Changes in this era have given rise to many trends, especially in the beauty sector, such as skincare and makeup, which are starting to be popular with the public. This trend is also followed by several artists or influencers who initially only promoted beauty products and eventually produced their own brands of beauty products or are also known as prosumers. This prosumer trend is followed by Madame Gie, the brand from artist Gisella Anastasia. The target of this study is to observe the impact of brand image and consumer satisfaction on customer satisfaction on social media. Unlike other beauty brands, Madam Gie, which is owned by Gisella Anastasia, is also able to compete in this digital era with the help of social media such as Instagram which can ultimately give rise to a new phenomenon, namely prosumers and the existing brand image is also an important factor for customer satisfaction because this only happens. on social media. This study used a quantitative method using a convenience sampling technique, the population was followers of the Madam Gie brand on Instagram. Next, the data obtained was processed using the SPSS application with a multiple linear regression test. This study found that brand image and prosumer variables had a positive impact on consumer satisfaction. Of the two independent variables, prosumers have a stronger influence in building customer satisfaction. Clear information about products and consumers who understand the beauty products needed by the market increase customer satisfaction.